Improving patient-centered communication of the borderline personality disorder diagnosis. (2nd January 2016) - Sulzer, Sandra H.; Muenchow, Elizabeth; Potvin, Annabelle; Harris, Jessica; Gigot, Grant
Abstract: Background : Borderline personality disorder (BPD) has historically been difficult to diagnose, and laden with stigma, leading to a variety of clinical responses to patients who present with symptoms. Aims : (1) To understand how clinicians communicate the diagnosis of BPD with patients. (2) To compare these practices with patient communication preferences. (3) To use patient preferences to evaluate clinician practices. Methods : Semi-structured interviews with mental health care providers and experts ( n  = 32) were compared with patients ( n  = 10) and primary patient-written accounts ( n  = 22). Grounded theory was used to explore causal pathways between clinical practice and patient responses. Results : The majority of clinicians sampled did not actively share the BPD diagnosis with their patients, even when they felt it was the most appropriate diagnosis. The majority of patients wanted to be told that they had the disorder, as well as have their providers discuss the stigma they would face. Patients who later discovered that their diagnosis had been withheld consistently left treatment. Conclusions : Clinicians believed that by not using the BPD label they were acknowledging or sidestepping the stigma of the condition. However, from the perspective of patients, open communication was essential for maintaining a therapeutic relationship.